2016
DOI: 10.1007/s12594-016-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal Gradients and Heat Flow Variations in Parts of the Eastern Niger Delta, Nigeria

Abstract: Geothermal gradients and present day heat flow values were evaluated for about seventy one wells in parts of the eastern Niger delta, using reservoir and corrected bottom – hole temperatures data and other data collected from the wells. The results showed that the geothermal gradients in the shallow/continental sections in the Niger delta vary between 10 - 18° C/km onshore, increasing to about 24° C/km seawards, southwards and eastwards. In the deeper (marine/paralic) section, geothermal gradients vary between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Borehole temperature data of the two studied wells were not available. Nevertheless, the average geothermal gradient 39.6 °C/km -1 of the neighbouring Afowo-1 well located on coast north of the X well (Avbovbo, 1978, Onuoha andOfoegbu, 1987), the heat flow of 59.5 + 10.9 mW/m 2 in the Gulf of Guinea area (Herman et al, 1997), the heat flow of 50mW/m 2 reported along the margin of Cote d'Ivoire, Togo and Nigeria, (Macgregor et al, 2003) and the average heat flow of 42.5 mW/m 2 in the contiguous Niger Delta (Odumodu and Mode, 2016) were used as control for the initial modelling based on their proximities and similar tectonic history with the Dahomey Basin. The geothermal gradient in the Afowo-1 (Dahomey Basin) and average heat of Gulf of Guinea basins was described to be higher than some part of the contiguous Niger Delta Basin.…”
Section: Calibration Datamentioning
confidence: 99%
“…Borehole temperature data of the two studied wells were not available. Nevertheless, the average geothermal gradient 39.6 °C/km -1 of the neighbouring Afowo-1 well located on coast north of the X well (Avbovbo, 1978, Onuoha andOfoegbu, 1987), the heat flow of 59.5 + 10.9 mW/m 2 in the Gulf of Guinea area (Herman et al, 1997), the heat flow of 50mW/m 2 reported along the margin of Cote d'Ivoire, Togo and Nigeria, (Macgregor et al, 2003) and the average heat flow of 42.5 mW/m 2 in the contiguous Niger Delta (Odumodu and Mode, 2016) were used as control for the initial modelling based on their proximities and similar tectonic history with the Dahomey Basin. The geothermal gradient in the Afowo-1 (Dahomey Basin) and average heat of Gulf of Guinea basins was described to be higher than some part of the contiguous Niger Delta Basin.…”
Section: Calibration Datamentioning
confidence: 99%
“…The lithostratigraphy of the Tertiary Niger Delta can be divided into three major units; Akata, Agbada, and Benin formations with depositional environments ranging from marine, transitional and continental settings respectively. Their ages range from Eocene to Recent, but they transgress time boundaries [8]. This region due to its hydrocarbon proliferation, then has 'depo-belts'; depositional belts or "depo belts" consists of a series of off-lapping siliciclastic sedimentation cycles or mega-sedimentary belts.…”
Section: Geologic Setting Of Niger Deltamentioning
confidence: 99%
“…Evammy, et al [9] referred to this structure as mega structure while [10] were the first to call them depo-belts. There are seven regional depo-belts which are discerned along the north-south axis of the Niger Delta, each with its own sedimentation, deformation and petroleum history [8], and the activity in each depo-belts has progressed in time and space toward the south-south west through stepwise alluvial progradation facilitated by large scale withdrawal and forward movement of the underlying shale. These depo-belts include; the Northern Delta, the Greater Ughelli, the Central Swamp I&II, the Coastal Swamp I&II, and the Offshore depo-belts [8].…”
Section: Geologic Setting Of Niger Deltamentioning
confidence: 99%
“…Several researchers used magnetic data to evaluate spectral CPD in different parts of the world in order to explore gas, oil and others resources [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In this paper, we estimate CPD, geothermal gradient, and heat flow values using spectrum analysis of the Grid Earth Magnetic Anomaly (EMAG2) for geothermal investigation in the Adamawa volcanic area.…”
Section: Introductionmentioning
confidence: 99%